The Influence of The Edufun Cervix Care Package on The Knowledge, Attitude, and Practice Regarding The Human Papillomavirus Vaccine and Cervical Cancer among Elementary School Female Students - Afirah, Ananda Lulu; Samaria, Dora; Desmawati, Desmawati; Marcelina, Lina Ayu (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2025)
Cervical cancer is a disease caused by the Human papillomavirus (HPV) infection that affects the cervix. The government has made efforts in the primary prevention of cervical cancer through HPV vaccination as a national immunization program aimed at girls aged 9-14 years. The provision of education related to HPV vaccination is often focused solely on parents, resulting in a lack of knowledge among children about HPV vaccination, which will influence their attitudes and practices regarding HPV vaccination and cervical cancer. This study examines the effects of the Edufun Cervix Care package on the Knowledge, Attitude, and Practice Regarding Human Papillomavirus Vaccination and Cervical Cancer among elementary school female students in Bekasi. This quantitative study uses a Quasi-Experimental One-Group Pretest-Posttest design. The study sample consists of 70 respondents selected through a total sampling technique. The results of the Wilcoxon test on the knowledge variable (CI 95% = 13.000-16.000, P-value 0.000), attitude (CI 95% = 3.000-5.000, P-value 0.000), and practice (CI 95% = 1.500-2.500, P-value 0.000). The research findings indicate a significant effect of the Edufun Cervix Care package on knowledge, attitude, and practice regarding Human Papillomavirus and Cervical Cancer among elementary school female students in Bekasi, marked by a P-value <0.05. It is hoped that future researchers will utilize different research designs and include parents as respondents in the study.